Interval Timing in Pediatric Multiple Sclerosis: Impaired in the Subsecond Range but Unimpaired in the One-Second Range - Troche, Stefan J.; Kapanci, Tugba; Rammsayer, Thomas H.; Kesseler, Carl P. A.; Häusler, Martin Georg; Geis, Tobias; Schimmel, Mareike; Elpers, Christiane; Kreth, Jonas H.; Thiels, Charlotte; Rostásy, Kevin (Frontiers in Neurology, 2020)
Background: For adult multiple sclerosis (MS) patients, impaired temporal processing of simultaneity/successiveness has been frequently reported while interval timing has been investigated neither in adult nor pediatric MS patients. We aimed to extent previous research in two ways. First, we focused on interval timing (instead of simultaneity/successiveness) and differentiated between sensory-automatic processing of intervals in the sub-second range and cognitive processing of intervals in the one-second range. Second, we investigated whether impaired temporal information processing would also be observable in pediatric MS patients’ interval timing in the sub-second and in the one-second range. Methods: Participants were Ttwenty-two pediatric MS patients and 22 healthy controls, matched for age, gender and psychometric intelligence as measured by the Culture Fair Test 20-R. They completed two auditory interval timing tasks with stimuli in the sub-second and in the one-second range, respectively, as well as a frequency discrimination task. Results: Pediatric MS patients showed impaired interval timing in the sub-second range compared to healthy controls with a mean difference of the difference limen (DL) of 6.3 ms, 95% CI [1.7, 10.9 ms], and an effect size of Cohen's d = .830. The two groups did not differ significantly in interval timing in the one-second range (mean difference of the DL = 26.9 ms, 95% CI [-14.2, 67.9 ms], Cohen's d = .399) nor in frequency discrimination (mean difference of the DL = 0.4 Hz, 95% CI [-1.1, 1.9 Hz], Cohen's d = .158). Conclusion: The results indicate that especially the sensory-automatic processing of intervals in the sub-second range but not the cognitive processing of longer intervals is impaired in pediatric MS patients. This differential pattern of results is unlikely to be explained by general deficits of auditory information processing. A tentative explanation, to be tested in future studies, points to subcortical deficits in pediatric MS patients, which might also underlie deficits in speech and visuomotor coordination typically reported in pediatric MS patients.